2010
DOI: 10.1155/2010/254032
|View full text |Cite
|
Sign up to set email alerts
|

DTI Parameter Optimisation for Acquisition at 1.5T: SNR Analysis and Clinical Application

Abstract: Background. Magnetic Resonance (MR) diffusion tensor imaging (DTI) is able to quantify in vivo tissue microstructure properties and to detect disease related pathology of the central nervous system. Nevertheless, DTI is limited by low spatial resolution associated with its low signal-to-noise-ratio (SNR). Aim. The aim is to select a DTI sequence for brain clinical studies, optimizing SNR and resolution. Methods and Results. We applied 6 methods for SNR computation in 26 DTI sequences with different parameters… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
21
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 30 publications
4
21
0
Order By: Relevance
“…Our findings also matched with previous work on SNR assessment (Laganà et al 2010;Lazar & Alexander 2003). It is also observed that modifications to the b-value, in our case it ranged from 200 to 500 s/mm 2 , not much affect the SNR.…”
Section: Assessment Of Snrsupporting
confidence: 92%
See 1 more Smart Citation
“…Our findings also matched with previous work on SNR assessment (Laganà et al 2010;Lazar & Alexander 2003). It is also observed that modifications to the b-value, in our case it ranged from 200 to 500 s/mm 2 , not much affect the SNR.…”
Section: Assessment Of Snrsupporting
confidence: 92%
“…In order to obtain the optimal parameters, assessment was performed on the SNR and then ADC and FA values of the data images. Due consideration was given to a combination of parameters yielding sufficient SNR as well as DTI values which are comparable to those obtained from previous reported studies (Alexander & Barker 2005;Hunsche et al, 2001;Laganà et al 2010;Lazar & Alexander 2003;Löbel et al 2009). The present investigation was performed on phantom and human volunteer.…”
Section: Introductionmentioning
confidence: 60%
“…org, Martinos Center for Biomedical Imaging, Massachusetts General (Wang et al, 2007)), a recently constructed software toolbox which provides precise diffusion imaging analysis and visualization capabilities (Granziera et al, 2009;Wedeen et al, 2008;Wahl et al, 2009;Vishwas et al, 2010;Lagana et al, 2010;Nezamzadeh et al, 2010). Diffusion tensor estimation was performed using the linear least-squares fitting method (Wang et al, 2007).…”
Section: Tractographymentioning
confidence: 99%
“…2,3,12 As such, there has been a desire to obtain improved resolution images with higher SNR. [47][48][49] The current study benefited in this regard from the use of ex vivo scans; however, additional resolution and improved SNR might be obtained with new coil designs and improved image sequences. Although image quality is important, especially with the use of the lower quality in vivo scans, the current results suggest that a whole cord ROI provides reasonable estimates of useful DTI metrics.…”
Section: Study Limitationsmentioning
confidence: 99%